2018
DOI: 10.1029/2018gl078781
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Precipitation and Cross‐Equatorial Heat Transport in Response to Localized Heating: Basin and Hemisphere Dependence

Abstract: A heat source is applied to different surface locations in a fully coupled climate model to study the cross‐equatorial energy transport and tropical precipitation responses. Remarkably different tropical precipitation responses are seen, varying from a large shift toward, to a small shift away from, the heated hemisphere. These differences are dominated by changes in top‐of‐atmosphere radiation, with some contribution from changes in ocean cross‐equatorial heat flux. The atmospheric fraction of the total cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Radiative feedbacks are known to modulate the equilibrium tropical response forced from the extratropics (e.g., Kang et al 2008;Zhang et al 2010;Seo et al 2014;Shaw et al 2015;White et al 2018). However, our experiments with a periodic extratropical forcing show that the TOA radiative flux plays a limited role in modulating the degree of tropical response due to a strong cancelation between the clear-sky component (F CLR ; dashdotted) and the cloud radiative effect (F CLD ; dashed) (Fig.…”
Section: Effect Of Radiative Feedbacks On the Extratropics-totropics ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Radiative feedbacks are known to modulate the equilibrium tropical response forced from the extratropics (e.g., Kang et al 2008;Zhang et al 2010;Seo et al 2014;Shaw et al 2015;White et al 2018). However, our experiments with a periodic extratropical forcing show that the TOA radiative flux plays a limited role in modulating the degree of tropical response due to a strong cancelation between the clear-sky component (F CLR ; dashdotted) and the cloud radiative effect (F CLD ; dashed) (Fig.…”
Section: Effect Of Radiative Feedbacks On the Extratropics-totropics ...mentioning
confidence: 99%
“…The extratropical impact on the tropics may have been overemphasized considering that earlier modeling studies assumed a passive ocean. How ocean dynamics modulates the extratropics-to-tropics teleconnection is an active area of current research (e.g., Green and Marshall 2017;Schneider 2017;Hawcroft et al 2017;Kang et al 2018a,b;White et al 2018;Green et al 2019;Yu and Pritchard 2019;Stuecker et al 2020;Kang 2020) and is the focus of the Extratropical-Tropical Model Intercomparison Project (Kang et al 2019(Kang et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the bulk of the cross‐equatorial transport was performed by the ocean. Previous research has suggested that the ocean does most of the cross‐equatorial transport when heat uptake is skewed toward the SH, while the atmosphere dominates when uptake occurs primarily in the NH (McFarlane & Frierson, ; White et al, ). Our results suggest that the ocean will dominate when heat is preferentially added to the SH (Figure f) or removed from the NH (Figure e).…”
Section: The Excess Heat Budgetmentioning
confidence: 99%
“…As an alternative approach, ETIN-MIP proposes to selectively perturb three target regions of persistent model biases in fully coupled models. Previous studies have adopted a similar approach, but used one fully coupled climate model (e.g., Hawcroft et al 2018;Xiang et al 2018;White et al 2018). ETIN-MIP will cast light on which regions are particularly important and sensitive to energy perturbations/biases in the context of their teleconnections and whether this sensitivity is robust by investigating causes of intermodel diversity and the specific processes that govern any spread in the models' response.…”
mentioning
confidence: 99%